Post-endoscopic biliary sphincterotomy bleeding: an interventional radiology approach. (December 2013) - Dunne, Ruth; McCarthy, Eoghan; Joyce, Eimear; McEniff, Niall; Guiney, Michael; Ryan, J Mark; Beddy, Peter
Background: Endoscopic sphincterotomy is an integral component of endoscopic retrograde cholangiopancreatography. Post-sphincterotomy hemorrhage is a recognized complication. First line treatment involves a variety of endoscopic techniques performed at the time of sphincterotomy. If these are not successful, transcatheter arterial embolization or open surgical vessel ligation are therapeutic considerations. Purpose: To evaluate the technical and clinical success of transcatheter arterial embolization via micro coils in the management of bleeding post-endoscopic sphincterotomy (ES). Material and Methods: An 8-year retrospective review of all patients referred for transcatheter arterial embolization (TAE) for management of post-ES bleeding not controlled by endoscopy was performed. We analyzed the findings at endoscopy, angiography, interventional procedure, and the technical and clinical success. Results: Twelve embolization procedures were performed in 11 patients. Technical success was achieved in 11 of 12 procedures. Branches embolized included the gastroduodenal artery (GDA) in 11 cases, the superior pancreaticoduodenal artery (SPDA) in one case, and the inferior pancreaticoduodenal artery (IPDA) in four cases. Clinical success was achieved in 10 of 11 patients. One patient was referred for surgical intervention due to rebleeding from the IPDA. Conclusion: Our experience demonstrates that TAE can effectively control bleeding post-ES avoiding the need for invasive surgery in most patients.